Pengaruh Service Quality Dan Social Media Marketing Terhadap Kepuasan Konsumen (Studi Kasus di Suara Coffee & Space Sei Agul Ujung) - Br. Tarigan, Roudhatul Dea Ersada; Khairunnisak, Khairunnisak (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2024)
This study aims to determine the effect of Service Quality and Social Media Marketing on customer satisfaction at Suara Coffee Space Sei Agul Ujung. This type of research is descriptive with a quantitative approach. The number of samples in this study amounted to 50 respondents taken from 618 total population, namely consumers of Suara Coffee Space Sei Agul Ujung from January - July 2023. Based on the partial t test results, the Service Quality variable has a positive and significant effect on the Consumer Satisfaction variable. For the t test on the Social Media Merketing variable partially does not have a significant effect on the Consumer Satisfaction variable. Based on the F test, it is obtained that the Service Quality variable and the Social Media Marketing variable simultaneously have a positive and significant effect on the Consumer Satisfaction variable. The Adjusted R Square value obtained is 0.836. Coefficient of Determination, it is obtained that 83.6% of the Consumer Satisfaction variable can be explained by the Service Quality variable and the Social Media Marketing variable, the remaining 16.4% is influenced by other factors not explained in this study.